THE NATURE OF DUCTILE DEFORMATION IN THE PHYLLITE-QUARTZITE UNIT (EXTERNAL HELLENIDES) - Xypolias, P.; Chatzaras, V. (Bulletin of the Geological Society of Greece, 2010)
This work describes the nature of ductile deformation in the Phyllite-Quartzite (PQ) unit in terms of structural evolution and spatial variation of finite strain and vorticity of flow. The PQ unit is affected by at least three ductile deformation (D1, 2, 3) phases. However, the D2 is the dominant phase resulting in the formation of a penetrative foliation (S2) which is by far the most common structural feature in all scales of observation. A stretching lineation (L2), which trends perpendicular to the structural grain of the belt, is well-developed within the S2 plane. Numerous kinematic criteria clearly indicate west (or south)-directed transport of the PQ unit during D2. This phase is also characterized by a systematic non-linear increase of strain ratio (Rxz) with proximity to the Basal thrust. Spatial variation of kinematic vorticity number reveals an increase of pure shear component of D2 deformation towards the middle structural levels of the unit. These results are used to discuss the validity of various geodynamic models related to the exhumation of the PQ unit.